Constructing Desired Vertical Component Distribution Within a PBDB-T:ITIC-M Photoactive Layer via Fine-Tuning the Surface Free Energy of a Titanium Chelate Cathode Buffer Layer - Bai, Yiming; Yang, Bo; Chen, Xiaohan; Wang, Fuzhi; Hayat, Tasawar; Alsaedi, Ahmed; Tan, Zhan'ao (Frontiers in Chemistry, 2018)
Rationally controlling the vertical component distribution of photoactive layer is crucial for efficient polymer solar cells (PSCs). Herein, fine tuning the surface free energy (SFE) of the titanium(IV) oxide bis(2,4-pentanedionate) (TOPD) cathode buffer layer is proposed to achieve a desired perpendicular component distribution for PBDB-T:ITIC-M photoactive layer. Owens-Wendt method is adopted to precisely calculate the SFE of TOPD film jointly based on the water contact angle and the diiodomethane contact angle. We find that the SFE of TOPD film increases obviously as the annealing temperature rises, and the subtle SFE change causes the profound vertical component distribution within the bulk region of PBDB-T:ITIC-M. The results of secondary-ion mass spectroscopy visibly demonstrate that the TOPD film with a SFE of 48.71mJ/cm2, which is very close to that of the ITIC film (43.98 mJ/cm2), tends to form desired vertical component distribution. Consequently, compared with the conventional bulk heterojunction devices, the power conversion efficiency increased from 9.00% to 10.20% benefiting from the short circuit current density increased from 14.76 to 16.88 mA/cm2. Our findings confirm that the SFE adjustment is an effective way of constructing the desired vertical component distribution and therefore achieving high-efficiency PSCs.